Núcleo de pesquisa em suínos como centro formador de recursos humanos para a suinocultura do futuro - Leal, Diego Feitosa; Muro, Bruno Bracco Donatelli; Martins, Simone Maria Massami Kitamura; Morenoi, Andrea Micke; Moretti, Aníbal Sant’Anna; Andrade, André Furugen Cesar de (Revista de Graduação USP, 2017)
Pig production has gained worldwide notoriety for using cutting-edge technologies aiming not only to increase its productivity and profitability but also to lessen the impact it causes on the environment. In this scenario, Brazil also plays a lead role in global pig production, occupying the forth position in the world ranking of pork production and also of pork exporting, hence, the importance of the pork industry becomes very clear since it is major source of wealth to Brazil’s economy, creating thousands of direct and indirect jobs which contribute to socioeconomic development. Thus, it becomes vital to form highly skilled human resources capable of working in an assertive manner on this field, advancing even more the pork industry and, consequently, the development of the country. To attend this demand, the Swine Research Center was created as a result of the merging of three laboratories (Laboratório de Pesquisa em Suínos; Laboratório de Andrologia e Tecnologia de Embriões Suínos; Laboratório de Sanidade Suína e Virologia), with the main objective of permitting that the undergraduate students could have a hands-on experience on the pig production field. Nowadays, undergraduate students can take part on various activities similar to those of a commercial pig farm, always monitored by faculty and post graduate students.